Research on integrated power generation control system based on wind, rainwater and energy store battery. (September 2019) - Hao, Zhongjia; He, Longying; Shen, Lumin; Zhong, Jie; Chen, Pengpeng
Abstract: The exploitation and utilization of new energy is the current trend of the energy industry. By analyzing the characteristics of wind energy, rainwater energy, graphene and energy store battery, an overall scheme of wind, rainwater and energy store integrated power generation system for urban buildings is designed, so is its control system. The design of control system includes hardware design and software design. By this control system, it achieves the goal of charge control and discharge control. This system takes the microcontroller as the data acquisition and controller, the data which has processed is displayed in the screen, by this SX1278 wireless communication module, and the data is transmitted to the computer.